A Risk Analysis and Ranking Application for Lifting Vehicles Used in Construction Sites with Integrated AHP and Fine-Kinney Approach - Yilmaz, Fatih; Ozcan, Mehmet Selim (LUBLIN UNIV TECHNOLOGY, POLAND, 2019)
Risk scoring methods applied in risk assessments used in Turkey, differ from each other in terms of analysis methods, scoring the risks, presumption and sensitivity levels. This article aims to eliminate the effects of divergent results of different risk analyses of lifting equipments used in the building industry and develop a practical hybrid risk analysis and ranking method. In this study risks of lifting equipments used in the building industry were scored by conventional Fine-Kenney risk analysis method first. Secondly, with the experience of previous accidents on construction sites, the reasons of accidents were sorted into 7 main criteria, which being 'Demographic', 'Behavioral', 'Machine Related', 'Working Environment Related', 'Economical', 'Administrative' and 'Organizational' criteria and related sub-criteria. Developing these criteria was supported by the experience of inspections carried out by labour inspectors. The weighted scores of these criteria were calculated by AHP method using a questionnaire applied to 14 experienced labor inspectors. The weighted scores obtained by the analytical hierarchy process method (AHP) were multiplied by the scores obtained by Fine-Kinney risk assessment method and a new integrated risk assessment and ranking application was introduced. With this application, a different priority rank was created and which risk to be eliminated primarily was determined.
Keywords: analytical hierarchy process; lifting equipments; fine-kinney; occupational health and safety; integrated risk analysis; ranking method; FUZZY AHP; OCCUPATIONAL-SAFETY; DECISION; SELECTION; CRITERIA; Engineering